2022
DOI: 10.48550/arxiv.2208.09341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The inheritance of energy conditions: Revisiting no-go theorems in string compactifications

Abstract: One of the fundamental challenges in string theory is to derive realistic four-dimensional cosmological backgrounds from it and it has been recently shown that there are strict consistency conditions which must be satisfied in string compactifications, thus constraining its possible lowenergy backgrounds. In this work, we focus on energy conditions as covariant and background independent consistency requirements in order to classify possible backgrounds coming from low-energy string theory in two steps. Firstl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Having said that, though, we also remark that our string inspired cosmology at late epochs, which has been the focus of our work in this article, has its origin in supergravity theories which describe low-energy effective string theories at early times. In [137], it has been argued that higher-dimensional string-compatible supergravity actions, corresponding to the standard content of the massless string spectrum, as in our case in this article, do satisfy all the energy conditions, provided quantum corrections are ignored. Such higher-dimensional energy conditions might induce the preservation of the four-dimensional energy conditions, so we might expect this to characterize our models.…”
Section: Energy Conditions and Tcc In The Strvmmentioning
confidence: 66%
“…Having said that, though, we also remark that our string inspired cosmology at late epochs, which has been the focus of our work in this article, has its origin in supergravity theories which describe low-energy effective string theories at early times. In [137], it has been argued that higher-dimensional string-compatible supergravity actions, corresponding to the standard content of the massless string spectrum, as in our case in this article, do satisfy all the energy conditions, provided quantum corrections are ignored. Such higher-dimensional energy conditions might induce the preservation of the four-dimensional energy conditions, so we might expect this to characterize our models.…”
Section: Energy Conditions and Tcc In The Strvmmentioning
confidence: 66%
“…A key open issue is a clear derivation of VECROs in cosmology from superstring theory. At a superficial level, our proposed gas of VECROs is in tension with energy conditions for an effective four space-time dimensional theory derived from string theory [48,49], where it is shown that the Null Energy Condition (NEC) must be obeyed. While our total energy density obeys the NEC, the gas of VECROs does not since it has negative energy density.…”
Section: Discussionmentioning
confidence: 99%
“…While our total energy density obeys the NEC, the gas of VECROs does not since it has negative energy density. The assumptions made in [48,49] on the continuity properties of the scale factor are obeyed in our model, our VECROs are quantum objects, and hence the analysis of [48,49] does not directly apply. Nevertheless, this issue requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Such transient acceleration is in fact generic in flux compactifications, see [11] for a review, although de Sitter space is still ruled out by the SEC, if the time-independence of the 4d Newton's constant is obeyed in a conventional way [12]. If instead the time-independence of the 4d Newton's constant is obeyed in an averaged way, even de Sitter space is not ruled out by the SEC, although the so-called dominant energy condition does rule out non-singular de Sitter compactifications [13] (see also [14,15] for a recent discussion on energy conditions).…”
Section: Jhep01(2023)033mentioning
confidence: 99%